Higiene Sanitasi Penjamah Makanan Di Citaringgul Kabupaten Bogor : Hygiene and Sanitation of Food Handlers in Citaringgul Village, Bogor Regency - Silvia Awaliyah, Vira Tazkia Mubarokah; Kahar, Kahar (Media Publikasi Cendekia Indonesia, 2024)
Background: Based on the BPOM RI report in 2020, there were 45 extraordinary food poisoning events (KLB KP), In addition, food poisoning outbreaks in Bogor Regency occurred 5 times in 2019, with a total of 141 cases in various villages. Aims: to determine the description of sanitary hygiene of food handlers in Citaringgul Village, Bogor Regency. Methods: This research method is descriptive. The population and sample in this study were 8 food handlers, and this study used univariate analysis. Information was obtained from food handlers and made observations in the area around food handlers to see firsthand the environmental conditions of food handlers and how food handlers process food. Results: Food Handler stands were 6 Food Handlers in the good category with a percentage of 75%. And 2 Food Handlers in the sufficient category with a percentage of 25%, so that the results of all aspects of observation are classified as good. In the respondent's knowledge category, there were 5 respondents in the good category with a percentage of 63%, and 3 respondents in the sufficient category with a percentage of 37%, so that the knowledge aspect was classified as good. In the respondent's attitude category, it is dominated by the good attitude category with a percentage of 75%. And there are 2 frequencies in the very good category with a percentage of 25%, so that the attitude category is classified as good. In the behavior category, the results obtained were 6 respondents in the good category with a percentage of 75% and 2 respondents in the sufficient category with a percentage of 25%. Conclusion: aspect of the Food Handler is classified as good so that the recommendations are that it needs to be improved on components that have not met the requirements.